Outage Probability of Dual-Hop Multiple Antenna Relay Systems with Interference at the Relay and Destination - Mengmeng Liu; Jianhua Zhang; Ping Zhang (International Journal of Antennas and Propagation)
This paper analyzes the outage performance of a dual-hop relaying system in which the relay is equipped with multiple antennas, while the source and destination have a single antenna. New exact closed-form expressions for the outage probability of both the amplify-and-forward (AF) and the decode-and-forward (DF) relaying systems are derived, assuming that the relay and destination are impaired by cochannel interferers and additive white Gaussian noise (AWGN). Numerical results are presented to verify the theoretical analysis.